هل المنطق الأرسطي صوري حقاً؟ - صالح رشيد (Latakia University Journal - Arts and Humanities Sciences Series, 2018)
يحاول هذا البحث تبيان أن نظرية القياس الأرسطية لم تكن نظرية صورية محضة، وأن العلاقة بين المنطق الأرسطي والمنطق الرياضي، بالرغم من وجود بعض القضايا المشتركة، علاقة قطيعة وليست علاقة استمرار. كما يحاول دحض أطروحة فيلسوف المنطق يان لوكاشيفتش، التي تؤكد أن نظرية القياس الأرسطية نظرية صورية رياضية. وذلك من خلال النقاط الآتية: 1- أن منطق أرسطو ذو نشأة ميتافيزيقية وليس له علاقة بالأنساق الرياضية. 2- أن عملية رد الأقيسة ليست عملية جوهرية في القياس الأرسطي، كما يحاول أن يبين لوكاشيفتش. 3- أن نظرية القياس الأرسطية لا تنتمي إلى المنطق الصوري، وإنما إلى تاريخ المنطق. This research tries to prove that Aristotle’s syllogistic theory was not pure formal logical theory, and that the relationship between Aristotle’s logic and the mathematical logic spite of some common matters, is relation of difference, and not relation of continuity. The research falsifies the opinion of Yan Lukasivich that says that Aristotle’s syllogistic theory does not differ from modern, logical and mathematical theories depending on the following points: 1- Aristotle’s logic is metaphysical, and has no relation with the modern, mathematical system. 2- The process of falsification, or change syllogistics is not an essential process in the Aristotle’s syllogistic theory. 3- Aristotle’s syllogistic theory does not belong to a formal logic, but it belongs to history of logic.